2021
DOI: 10.3390/molecules27010023
|View full text |Cite
|
Sign up to set email alerts
|

Give or Take: Effects of Electron-Accepting/-Withdrawing Groups in Red-Fluorescent BODIPY Molecular Rotors

Abstract: Mapping microviscosity, temperature, and polarity in biosystems is an important capability that can aid in disease detection. This can be achieved using fluorescent sensors based on a green-emitting BODIPY group. However, red fluorescent sensors are desired for convenient imaging of biological samples. It is known that phenyl substituents in the β position of the BODIPY core can shift the fluorescence spectra to longer wavelengths. In this research, we report how electron-withdrawing (EWG) and -donating (EDG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 58 publications
(107 reference statements)
0
11
0
Order By: Relevance
“…Such effect achieved by the introduction of electron-withdrawing groups was demonstrated previously. 24 We also note that results presented in Table 1 demonstrate that k nr is significantly faster than k r . Since all of the molecules in this study exhibit only slight solvatochromism (Fig.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Such effect achieved by the introduction of electron-withdrawing groups was demonstrated previously. 24 We also note that results presented in Table 1 demonstrate that k nr is significantly faster than k r . Since all of the molecules in this study exhibit only slight solvatochromism (Fig.…”
Section: Resultsmentioning
confidence: 72%
“…Modifying aand b-positions with aromatic moieties to red-shift the fluorescence wavelength, extinguished the sensitivity to viscosity, whilst increasing responsiveness to polarity. 24 The latter observation was taken in practice by Maleckaite ˙et al who synthesised and explored a red-emitting BODIPY polarity probe BP-PH-OMe modified with electrondonating 4-methoxyphenyl groups at the b,b 0 -positions of the BODIPY core. These results were the basis of this work, where we aimed to synthesise red-emitting polarity probes for sensing in lipid environment.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…There are several examples demonstrating the latest achievements in this field, e.g., BODIPY functionalized with lactose [ 21 ], phosphorylated BODIPY [ 22 ], diketopyrrolopyrrole-aza-BODIPY hybrids [ 23 ], N-BODIPY containing a para-nitrophenyl group at the meso position and a diamino-boron substituent with two tosyl pendant moieties [ 24 ], trifluoromethyl-substituted (i.e., with electron-withdrawing groups) and methoxy-substituted (with electron-donating groups) dyes [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A BODIPY core structure in molecular rotors grants large molar extinction coefficients, photostability and chemical inertness [ 17 , 18 , 19 ]. Furthermore, BODIPY-based probes can be easily functionalized at the appropriate positions to tune their sensitivity to micro-environment viscosity, polarity or temperature; increase the emission wavelength or Stokes shift; or direct the molecules to specific cells or organelles [ 20 , 21 , 22 , 23 , 24 , 25 ]. Recently, we demonstrated that the functionalization of meso -phenyl BODIPY (BDP-H) ( Figure 1 ) with a heavy-electron withdrawing –NO 2 group results in a viscosity-sensor with an extremely wide viscosity-sensitivity range (0.5–50,000 cP) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%